2020
DOI: 10.1186/s13063-020-4109-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astragalus injection and Salvia Miltiorrhiza injection on serum inflammatory markers in patients with stable coronary heart disease: a randomized controlled trial protocol

Abstract: Background: Coronary heart disease (CHD) is a clinical syndrome caused by coronary atherosclerosis (AS) or functional changes in coronary arteries. We have previously reported that astragaloside IV (in astragalus) and tanshinone IIA (in Salvia miltiorrhiza) improve myocardial ischemic injury. Methods: This study will employ the randomized, blinded, prospective, single-center experiments approach. Briefly, a total of 160 eligible patients will be equally randomized into three treatment groups and placebo contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Danshen is widely used in treating cardiovascular diseases, such as IHD. [42][43][44] In addition, Danshen possesses sedative and anxiolytic effects. 45 Therefore, we reasonably speculate that Danshen has the potential to treat concurrent IHD and depression, but its precise mechanism of action remains unknown, and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Danshen is widely used in treating cardiovascular diseases, such as IHD. [42][43][44] In addition, Danshen possesses sedative and anxiolytic effects. 45 Therefore, we reasonably speculate that Danshen has the potential to treat concurrent IHD and depression, but its precise mechanism of action remains unknown, and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…e study herein proved that applying Huayu Tongmai decoction on the basis of atorvastatin intervention could further improve the hs-CRP levels in patients. In the research by Luo et al, it was found Evidence-Based Complementary and Alternative Medicine that danshen root could effectively lower the hs-CRP levels in CHD patients and then improve their systemic inflammatory levels [19]. Xue et al also proved that golden thread could significantly lower the hs-CRP levels in rats to remarkably ameliorate the symptoms of carotid thrombosis [16].…”
Section: Discussionmentioning
confidence: 99%
“…The combined use of Astragalus membranaceus (Fisch.) Bunge and Salvia miltiorrhiza Bunge, along with other traditional Chinese medicals, can have a synergistic effect in treating cardiovascular diseases [ 21 ]. Tanshinone IIA (Ta-IIA), the main active ingredient in Salvia miltiorrhiza Bunge [ 19 , 22 , 23 ], and Astragaloside IV (As-IV), the main active ingredient in Astragalus membranaceus (Fisch.)…”
Section: Introductionmentioning
confidence: 99%